Molecular epidemiological survey of haemoglobinopathies in the Guangxi Zhuang Autonomous Region of southern China - Xiong, F; Sun, M; Zhang, X; Cai, R; Zhou, Y; Lou, J; Zeng, L; Sun, Q; Xiao, Q; Shang, X; Wei, X; Zhang, T; et al. (Clinical genetics, 2010)
Xiong F, Sun M, Zhang X, Cai R, Zhou Y, Lou J, Zeng L, Sun Q, Xiao Q, Shang X, Wei X, Zhang T, Chen P, Xu X. Molecular epidemiological survey of haemoglobinopathies in the Guangxi Zhuang Autonomous Region of southern China. Accurate and up‐to‐date data on the frequency of haemoglobinopathies among the populations of Guangxi Zhuang Autonomous Region, where haemoglobinopathies are most endemic in China, are required. In our study, a total of 5789 samples obtained from members of the Han, Zhang, and Yao ethnic groups in six geographical areas of Guangxi Province were analysed systematically in terms of both haematological and molecular parameters. The results presented that the total heterozygote frequency of thalassaemias and other haemoglobinopathies was 24.51%, of which 17.55% was due to α‐thalassaemia, 6.43% to β‐thalassaemia, 0.38% to structural haemoglobin variants, and 0.16% to δ‐thalassaemia. The mutational spectrum among the local population for each type of disorder was described, including the first report on the true prevalence of three silent α thalassemia defects, −α3.7/(4.78%), −α4.2/(1.61%) and Hb Westmead (αWSα/) (1.57%) and of δ‐thalassemia resulting from five novel and two rare mutations never before identified in Chinese individuals. Comparison of the frequencies of α‐globin mutations among the ethnic groups showed that there was a statistically significant difference between the Han (15.71%) and Zhuang (20.12%), and between the Han (15.71%) and Yao (20.84%) ethnic groups. In addition, we have performed the first extensive study of haematological parameters of the Hb Westmead mutation using a group of Chinese subjects with compound heterozygosity for this variant and an α‐thalassaemia deletion. The knowledge gained in this study will enable us to estimate the health burden in this high‐risk population and to elucidate the various genetic alterations that underlie haemoglobinopathies.